Oesophageal clearance of acid and bile: a combined radionuclide, pH, and Bilitec study. Issue 1 (18th December 2003) - Koek, G H; Vos, R; Flamen, P; Sifrim, D; Lammert, F; Vanbilloen, B; Janssens, J; Tack, J
Abstract : Background: Studies combining pH and Bilitec monitoring found a high prevalence of both acid and duodeno-gastro-oesophageal reflux in severe reflux disease. Clearance of refluxed material is a major defence mechanism against reflux. Several studies have been devoted to oesophageal acid clearance but oesophageal clearance of refluxed duodenal contents (DC) has rarely been addressed. Aim: To compare oesophageal acid and DC clearance. Methods: Ten healthy volunteers (five women, mean age 23 (1) years) were studied. Firstly, a balloon tip catheter, positioned in the duodenum under fluoroscopy, was used to aspirate DC after stimulation by a high caloric liquid meal (200 ml, 300 kcal). During the second session, pH and Bilitec probes were positioned 5 cm above the lower oesophageal sphincter and a small infusion catheter was introduced into the proximal oesophagus. The subject was placed supine under a gamma camera. One of two different solutions (DC mixed with 0.2 mCi Tc 99m pertechnetate or citric acid (pH 2) mixed with 0.2 mCi Tc 99m pertechnetate) was infused into the proximal oesophagus and the subject was instructed to swallow at 20 second intervals. Clearance was assessed using scintigraphy (dynamic acquisition, one frame per second in the anterior view; calculation of time to clear peak counts to background level), pH (time to pH<4) or Bilitec (time absorbance >0.14) monitoring, with or without continuous saliva aspiration. Each condition was studied twice in a randomised design; measurement time was four minutes, interrupted by water flushing, with a two minute rest period. Results are given as mean (SEM) and were compared by Student's t test and Pearson correlation. Results: Scintigraphic evaluation showed a volume clearance time of 29 (3) seconds for acid and 28 (9) seconds for DC (NS). Saliva aspiration had no significant influence on volume clearance of acid or DC (28 (4) and 30 (13) seconds, respectively; NS). pH monitoring showed an acid clearance time of 217 (15) seconds, which was significantly prolonged to 324 (30) seconds during saliva aspiration (p<0.05). Bilitec monitoring showed a DC clearance time of 131 (27) seconds, which was not significantly prolonged by saliva aspiration (176 (36) seconds; p = 0.08). DC clearance was faster than acid clearance, either without or with saliva aspiration (p<0.055 and p<0.05, respectively). Conclusions: Under experimental conditions, liquid acid and DC solutions have comparable volume clearances. Chemical clearance occurs slightly faster for DC than for acid, and saliva plays a major role in the clearance of acid only.